Globalisation and Its Implications for Agriculture, Food Security, and Poverty in Pakistan (The Pakistan Development Review, 2001)
The world trade liberalisation has been the major concern to almost all the international communities since very long due to the extensive trade restrictions imposed by the developed and industrial countries. These restrictions caused to create a very tough protectionist economic environment for all the countries [SESRTCIC (1995) and Chaudhary (2001)]. Pakistan is one of the founder members of the General Agreement on Tariffs and Trade (GATT) since 1948 and a signatory of Uruguay Round of Multilateral Trade Agreement (MTA) with Word Trade Organisation (WTO). The Agreement made significant progress in three major areas i.e. market liberalisation which could add approximately one percent of world real GDP (US$212-274 billion) and 10 percent to world trade upon full implementation of the Agreement, strengthening of rule and institutional structure, particularly the creation of WTO, which could decide on dispute and impairment of trade rules and principles, and integration of new areas into the multilateral trading system such as general agreements on trade in services (GATS) and trade-related intellectual property rights (TRIPs), trade-related investment measures (TRIMs) and the traditionally sensitive and contentious sectors (agriculture, and textile and clothing) [Abidin (1994); GATT (1994) and IMF (1994)]. The classical economists explained the welfare benefits of globalisation (by the specialisation and widening of markets through trade). Trade can bring settlement by allowing countries to take benefit of their comparative advantage, harvest the profit of scale economies and ensure competition, greater variety and potentially, more stable markets and prices. The free movement of capital directs resources towards their more productive use.